Experience and theory in advertising decisions among marketing managers - Garay-Acuña, Alonso (2023)
Marketing executives make constant decisions regarding advertising. However, scant literature has examined their understanding of how advertising works. This study analyzes whether the underlying reasoning in the advertising decisions of marketing executives is based on or is in line with the scientific literature on advertising functioning and effectiveness. A qualitative analysis and a structural coding analysis technique were conducted based on the propositions of a meta-analysis on advertising effectiveness focused on advertising inputs and outcomes. The study obtained data through interviews with marketing directors from various sectors. Findings indicate that marketing executives base their decisions on professional experience and implicit assumptions rather than on what the literature indicates. This study provides insights into the extent of marketing executives' understanding of how advertising works and how it influences their decisions.